Analysis of Online Reactions to the Proscription of IPOB as Terrorist Organization (Global Journal of Human-Social Science, 2018)
The classification of the Indigenous People of Biafra (IPOB) as a terrorist organisation has been condemned by those who felt government went overboard. The voice of these individuals and groups are so strident that it seemingly drowned the support accorded the proscription by those who believe that IPOB deserved to be so labelled. These divergent positions of newsmakers were examined since as opinion moulders they greatly influence the thinking of the populace towards any particular subject. The analysis was done within the framework of the democratic participant theory which posits that input of the people in public policy and decisions should matter. Using Google filters, the researcher x-rayed a sample of the reactions of newsmakers published online as news to answer four research questions, yielding among other things that government's designation of IPOB as terrorist organization was not popular, especially as a much more violent group -Fulani militia -recognized abroad as terrorist organization was not so classified locally. Therefore, this paper called on the authorities to be even handed when dealing with criminal groups irrespective of the part of Nigeria they come from, and advocates that government should give every segment of society a sense of belonging.
Keywords: analysis; online reactions; proscription; IPOB; terrorist organization